How does post-mortem imaging compare to autopsy, is this a relevant question?. (March 2016) - Morgan, Bruno; Rutty, Guy N.
Abstract: The rapid development of imaging techniques used for the investigation of death invites the question "how does imaging compare with autopsy". This paper is based on an invited talk given to the International Society of Forensic Radiology and Imaging in 2015 and attempts to show that this question cannot be answered, as it is in fact several questions depending on the circumstances of death. Review of the literature is fraught with difficulties due to the rapid evolution of technology, the varied circumstances of death investigation and the multiple possible post-mortem investigations that imaging can be compared with. The article focuses on the assessment of adult sudden natural death and suggests the questions that need to be answered. Highlights: Evidence of "efficacy" for a test does not imply it is effective in the real world. Direct comparisons between autopsy and imaging may give misleading results. Imaging is used in a wide variety of contexts, all with different questions. The level of accuracy required of an imaging test depends on the context. Research findings in one context may not be applicable in all contexts.